Thirty trillion cells : how your body really works - Thomas, Isabel, 1979- (Welbeck Editions, 2022)
"... provides a detailed look at the topic of the human body, covering of the body's major systems and organs, as well as looking at the cellular level and at the genetics that play a part in making us who we are."--